2020
DOI: 10.5194/egusphere-egu2020-13455
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Challenges in Constraining Future Change of Global Land Precipitation in CMIP6 Models

Abstract: <p><span>The Coupled Model Intercomparison Project Phase 5 (CMIP5) models have showed substantial inter-model spread in estimating annual global-mean precipitation change per one-degree greenhouse-gas-induced warming (precipitation sensitivity), ranging from -4.5</span><span>–4.2</span><span>%</span><sup><span>o</span></sup><span>C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…It is reported that the increase in GHG forcing caused enhanced monsoon rainfall by about 13% in the 22nd century, while the large-scale monsoon circulation became weak [22]. Coupled Model Intercomparison Model 5 (CMIP5) and CMIP6 strongly suggest that monsoon fed area, annual range, mean precipitation are likely to increase by the end of the 21 century [23,24]. The increase in the monsoon in the NH will be manifested by the earlier or unchanged onset dates and delayed retreat from land areas [25].…”
Section: Ism Response To Climate Changementioning
confidence: 99%
“…It is reported that the increase in GHG forcing caused enhanced monsoon rainfall by about 13% in the 22nd century, while the large-scale monsoon circulation became weak [22]. Coupled Model Intercomparison Model 5 (CMIP5) and CMIP6 strongly suggest that monsoon fed area, annual range, mean precipitation are likely to increase by the end of the 21 century [23,24]. The increase in the monsoon in the NH will be manifested by the earlier or unchanged onset dates and delayed retreat from land areas [25].…”
Section: Ism Response To Climate Changementioning
confidence: 99%